Lateral Lumbar Interbody Fusion for Ossification of the Yellow Ligament in the Lumbar Spine: First Reported Case - Fujii, Kengo (Case Rep Orthop, 2017)
When ossification of the yellow ligament (OYL) occurs in the lumbar spine and extends to the lateral wall of the spinal canal, facetectomy is required to remove all of the ossified lesion and achieve decompression. Subsequent posterior fixation with interbody fusion will then be necessary to prevent postoperative progression of the ossification and intervertebral instability. The technique of lateral lumbar interbody fusion (LLIF) has recently been introduced. Using this procedure, surgeons can avoid excess blood loss from the extradural venous plexus and detachment of the ossified lesion and the ventral dura mater is avoidable. We present a 55-year-old male patient with OYL at L3/4 and anterior spondylolisthesis of L4 vertebra, with concomitant ossification of the posterior longitudinal ligament, who presented with a severe gait disturbance. He underwent a 2-stage operation without complications: LLIF for L3/4 and L4/5 was performed at the initial surgery, and posterior decompression fixation using pedicle screws from L3 to L5 was performed at the second surgery. His postoperative progress was favorable, and his interbody fusion was deemed successful. Here, we present the first reported case of LLIF for OYL of the lumbar spine. This procedure can be a good option for OYL of the lumbar spine.